Analisis PDRB, Tingkat Pengangguran, Belanja Modal dan Rata-Rata Lama Sekolah terhadap IPM di Kabupaten Bangkalan - Alifah, Siti Nur; Imaningsih, Niniek (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The main objective of this study is to analyze the effect of GRDP, unemployment rate, capital expenditure and average length of schooling on the Human Development Index (IPM) ofBangkalan Regency. Observation data obtained from BPS Bangkalan Regency with time series 2010-2020. The data analysis technique used in this research is multiple linear regression analysis using the IBM SPSS version 26.0 program. The results of this study indicate that partially GRDP, unemployment rate and capital expenditure have no significant effect on HDI, but the average length of schooling has a positive and significant effect on HDI in Bangkalan Regency from 2010 to 2020. All variables have a simultaneous effect on HDI. This study also shows the importance of the role of capital expenditure, especially for the public service sector, so that it affects economic growth and provides access to small communities in the productive economic sector with the ultimate goal of improving the welfare of the local community.